T1‐ or T2‐weighted magnetic resonance imaging: what is the best choice to evaluate atrophy of the hippocampus?. (9th March 2018) - Fischbach‐Boulanger, C.; Fitsiori, A.; Noblet, V.; Baloglu, S.; Oesterle, H.; Draghici, S.; Philippi, N.; Duron, E.; Hanon, O.; Dietemann, J.‐L.; Blanc, F.; Kremer, S.
Abstract : Background and purpose: Magnetic resonance imaging is part of the diagnostic criteria for Alzheimer's disease (AD) through the evaluation of hippocampal atrophy. The objective of this study was to evaluate which sequence of T1‐weighted (T1WI) and T2‐weighted (T2WI) imaging allowed the best visual evaluation of hippocampal atrophy. Methods: Visual qualitative ratings of the hippocampus of 100 patients with mild cognitive impairment (MCI) and 50 patients with AD were made independently by four operators according to the medial temporal lobe atrophy score based either on T1WI or T2WI. These two evaluations were compared in terms of interobserver reproducibility, concordance with a quantitative volumetric measure, discrimination power between AD and MCI groups, and correlation with several neuropsychological tests. Results: The medial temporal lobe atrophy score evaluated on either T1WI or T2WI exhibited similar interobserver variability and accordance with quantitative volumetric evaluation. However, the visual evaluation on T2WI seemed to provide better discrimination power between AD and MCI groups for both left (T1WI, P  = 0.0001; T2WI, P  = 7.072 × 10 −5 ) and right (T1WI, P  = 0.008; T2WI, P  = 0.001) hippocampus, and a higher overall correlation with neuropsychological tests. Conclusions: The present study suggests that T2WI provides a more adequate visual rating of hippocampal atrophy.